Pemberdayaan Masyarakat Melalui BUMG Maju Jaya Di Gampong Peunaga Pasi Kabupaten Aceh Barat - Mustafa, Mustafa; Mursyidin, Mursyidin; Abidin, abidin; Alwi, Alwi; Chalid, Ibrahim (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
BUMG Maju Jaya in Gampong Peunaga Pasi is the only Village-Owned Enterprise (BUMDes) that has consistently sustained and developed compared to other BUMDes in Aceh Barat. As the first BUMDes established in the region, its sustainability and success reflect effective management practices while also highlighting the structural challenges faced by other BUMDes in achieving similar outcomes. The purpose of this study is to reveal the contribution of BUMG Maju Jaya in supporting community economic independence through the optimization of local coastal area potential. The study adopts a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that BUMG Maju Jaya has significantly enhanced both village and community income by managing water tourism and other supporting facilities. Active community participation and trust-based social management have been identified as key factors behind its success. Revenue from business units such as the waterboom, canteen, and other village assets has shown substantial growth. Additionally, the management of BUMG has made a substantial contribution to the development of social and human capital, including improving community skills, knowledge, and participation in economic programs. The recommendations derived from this study suggest that BUMG Maju Jaya can serve as a model for other BUMDes by disseminating best practices in trust-based governance, economic diversification, and sustainable community empowerment.